Metformin - A Panacea Pharmaceutical Agent through convergence revolution initiative - Prabhakaran, Sonia; Thirumal , Dhiviya; Jolius, Gimbun; Ranganathan, Balu (Informatics Publishing Limited, 2017)
Metformin has been known to the mankind for centuries. Metformin is the first line of drug of choice for the treatment of type 2 diabetes. Initial pharmaceutical therapy was for treating the frequent urinal problem which is a primary manifestation of diabetes. At the time of writing, metformin as an intervention is looked into for cardiovascular risks, polycystic ovary syndrome and breast cancer. Annual demand for Metformin is 23,000 Metric tons per annum. Nano Drug Delivery Systems (NDDS) has embarked into Metformin controlled and targeted delivery for breast cancer, pancreatic cancer and non-small cell lung cancer. Clinical estimation of the biological fluids by the FDA approved diagnostic laboratories use LC-MS/MS where blood samples estimate Metformin as an intact molecule easing the pressure of clinical trials result. Metformin was manufactured by a less known and low profile Aoron pharmaceutical, France not aware of the block buster drug hence the potential of technology development start-ups can neither be underwritten nor underestimated even when there is a very high rate (~90%) of failed biotech/biomed start-up ventures. The bloom of the French lilac (metformin) to blossom and flower for the cure of breast cancer by convergence revolution initiative with the integration of academia, hospital, technology business incubator, multinational corporation with the deliverance of a start-up company